Analysis of fatal cases of severe fever with thrombocytopenia syndrome in Jiangsu province, China, between 2011 and 2022: A retrospective study - Liang, Shuyi; Xie, Wei; Li, Zhifeng; Zhang, Nan; Wang, Xiaochen; Qin, Yuanfang; Bao, Changjun; Hu, Jianli (Frontiers in Public Health, 2023)
Severe fever with thrombocytopenia syndrome (SFTS) , an emerging acute infectious disease, is caused by a novel bunyavirus. In recent years, the number of SFTS cases increased obviously in Jiangsu province. Of note, the fatal cases were also getting more and more. This study elucidated epidemiological features of the fatal cases of SFTSV and fatal risk factors of SFTS cases accumulated up to twelve years in Jiangsu Province from 2011 to September, 2022. A total of 698 confirmed SFTS cases were reported with an increasing trend. Among them, a total of 43 death were reported.The fatal cases in Jiangsu Province were distributed in 12 districted counties from 2011 to 2022. Notably, the majority of deaths resided in Lishui county of Nanjing City. The median age of the deaths was 69 years with a range from 50 to 83 years. The majority of the deaths were farmers who lived in rural areas with mountainous and hilly. Multivariable Cox regression analysis revealed that older age(>70) and living in Lishui county were independent risk factors for fatal outcomes. Based on the study, the elderly who aged over 70 residing in Lishui County were the most high-risk group for SFTS. With an increased annual incidence over the last twelve years, SFTS remains a public health threat that should not be ignored. Further study is needed to look at meteorological factors in the natural foci.